EFIKASI DAN UJI SIFAT CAMPURAN HERBISIDA SAFLUFENACIL DAN TRIFLUDIMOXAZIN TERHADAP GULMA Ageratum conyzoides, Digitaria ciliaris, DAN Cyperus kyllingia - Cahyani, Dwi; Sembodo, Dad Resiworo Jekti; Sriyani, Nanik; Pujisiswanto, Hidayat; Susanto, Herry (JURNAL AGROTROPIKA, 2025)
This study aimed to evaluate the efficacy of single herbicides saflufenacil, trifludimoxazin, and their mixtures, as well as to determine the interaction characteristics of the saflufenacil and trifludimoxazin combination in weed control. The experiment was conducted in a Plastic House in Natar District, South Lampung Regency, from April to May 2025. A single-factor Randomized Block Design (RBD) was applied with 54 treatment combinations, consisting of 3 herbicide types at 6 dosage levels: single saflufenacil (0, 25, 50, 100, 200, and 400 g/ha), single trifludimoxazin (0, 12.5, 25, 50, 100, and 200 g/ha), and their mixtures (0, 37.5, 75, 150, 300, and 600 g/ha). Treatments were applied to 3 weed species: the broadleaf Ageratum conyzoides, the grass Digitaria ciliaris, and the sedge Cyperus kyllingia. Each treatment was replicated 6 times. The interaction analysis of herbicide mixtures was carried out using the Multiplicative Survival Model (MSM), since the two herbicides have different modes of action. The results showed that: (1) single saflufenacil was only effective in controlling Ageratum conyzoides at (25-400 g/ha). Single trifludimoxazin effectively controlled Ageratum conyzoides (12.5-200 g/ha), Digitaria ciliaris (200 g/ha), and Cyperus kyllingia (50-200 g/ha). The mixture of saflufenacil+trifludimoxazin effectively controlled Ageratum conyzoides (37.5-600 g/ha), Digitaria ciliaris (75-600 g/ha), and Cyperus kyllingia (300-600 g/ha). (2) With an expected LD50 value of 83.36, which was higher than the observed LD50 value of 67.33, a co-toxicity coefficient of 1.24 (>1) was obtained, indicating that the mixture exhibited a synergistic effect.